En quête de résonances, déployer l’écriture - Christine Bouissou (Communication)
The author discusses an experiment where the main challenge lay in breaking away from a field saturated with overly deterministic and tautological discourse to write for an audience of young female students, evoking another frame of reference where the imaginary is welcome and opening the door to dissemination and sharing. The author describes the key steps that all start with a research training group. This research is supported by a media, Internet, radio, and textual review hinging on a few key emerging references that are consolidated and reworked along the way.